Academic Senate Minutes 2005-04-28 - Academic Senate:::::::::
Chair report. Agenda amended and approved. Minutes deferred. Candidates for Graduation approved. Proposed Revised History/Social Sciences Single Subject Preparation Program approved. Update on WASC. Special Report on SFR: Orlick, Furukawa-Schlereth and Ochoa. Posthumous Certificate of Recognition for Caitlin Byrd approved. Access to Programs for Students with Disabilities Policy first reading waived. EPC report.